Lithium enhances post-stroke blood-brain barrier integrity, activates the MAPK/ERK1/2 pathway and alters immune cell migration in mice. (15th December 2020) - Haupt, Matteo; Zechmeister, Bozena; Bosche, Bert; Lieschke, Simone; Zheng, Xuan; Zhang, Lin; Venkataramani, Vivek; Jin, Fengyan; Hein, Katharina; Weber, Martin S.; Hermann, Dirk M.; Bähr, Mathias; et al.
Abstract: Lithium induces neuroprotection against cerebral ischemia, although the underlying mechanisms remain elusive. We have previously suggested a role for lithium in calcium regulation and (extra)cerebral vessel relaxation under non-ischemic conditions. Herein, we aimed to investigate whether or not lithium contributes to post-stroke stabilization of the blood-brain barrier (BBB) in mice. Using an oxygen-glucose-deprivation (OGD) model, we first analyzed the impact of lithium treatment on endothelial cells (EC) in vitro . Indeed, such treatment of EC exposed to OGD resulted in increased cell survival as well as in enhanced expression of tight junction proteins and P-glycoprotein. Additional in vivo studies demonstrated an increased stabilization of the BBB upon lithium treatment in stroke mice, as shown by a reduced Evans blue extravasation and an elevation of tight junction protein expression. Furthermore, stabilization of the BBB as a consequence of lithium treatment was associated with an inhibition of matrix metalloproteinase-9 activity, independent of calveolin-1 regulation. In line with this, flow cytometry analysis revealed that lithium treatment led to a decreased neutrophil invasion and an increased T cell extravasation from the blood compartment towards the brain parenchyma. We finally identified the pro-survival MAPK/ERK1/2 pathway as the key regulator of the impact of lithium on the BBB. In conclusion, we demonstrate for the first time that lithium is able to enhance post-stroke BBB integrity. Importantly, our work delivers novel insights into the exact mechanism of lithium-induced acute neuroprotection, providing critical information for future clinical trials involving lithium treatment in stroke patients. Graphical abstract: Image 1 Highlights: Lithium prevents oxygen-glucose-deprived endothelial cells from tight junction loss. Lithium stabilizes post-stroke blood-brain barrier via MAPK/ERK/pathway activation. Lithium decreases activity and expression of MMP-9 independent of caveolin-1. Lithium modulates post-stroke neutrophil and T cell extravasation via ICAM-1.